A descentralização da gestão ambiental pública: estudo de caso no município de Ribeirão Preto/SP - Saquy, Sammy Dutra (2020)
Nature conservation has been shown to be extremely important for the quality of life of the population with the maintenance of ecosystem services. There is pressure on public authorities to create, maintain, improve and increase actions in favor of the environment. A point that has been discussed is about these actions adapting to local peculiarities, making conservation of environmental resources increasingly viable, since Brazil has great heterogeneity in the characteristics and distribution of these resources throughout its territory. The decentralization of public environmental management transfers responsibilities from the Union to the states and from the states to the municipalities, in an attempt to achieve local environmental governance and strengthen social participation. The model of cooperative federalism in the country allows decentralization to occur without excluding cooperation between federal entities. The present study aimed to investigate the process of decentralization of environmental attributions and the fragmentation of environmental performance in different agencies and institutions within the public environmental management system in the city of Ribeirão Preto / SP. This study carried out a bibliographic and documentary survey and semi-structured interviews with the representatives of each environmental agency with a physical unit in the city of Ribeirão Preto, which were transcribed, and analyzed based on content analysis with the aid of the software. From the results obtained, it is possible to infer that decentralization in the city of Ribeirão Preto has its process supported by laws and has an institutional apparatus that makes it possible to achieve the objectives of this transfer of authority. The fragmentation was seen by the interviewees as a positive aspect when related to the specialization of the areas as a result of this process, however, efficiency in communication and interinstitutional cooperation is essential for public policies to function correctly. As one of the main points cited by the interviewees as a positive aspect, the proximity of the local government and the environmental agencies of the population enables social participation and provides easier access to the organs. On the other hand, this proximity to decision-making agencies in public environmental management can have negative consequences such as clientelistic practices that influence public authorities in order to seek private interests. Therefore, decentralization does not present itself as a problem, however, opportunistic actions by actors and sectors that take advantage of this process of transferring responsibilities to the local government generate negative consequences for sustainable development and collective interest, which may compromise the entire governance process. local environmental policy. Politicians with an active mandate have the power to influence environmental agencies, weakening them with the intention of hindering institutional actions or marginalizing the environmental issue. The lack of technical and financial resources at the municipal level compromises environmental defense and the local environmental governance process. These are major problems to be faced. In this way, environmental education must be worked on in search of changes in posture, mainly of the public power. The improvement of environmental decentralization is a great challenge and a permanent need in search of sustainability.